Eutanásia e crenças espirituais em estudantes de medicina - Alexandre Filipe Gonçalves de Sousa (2020)
Public debate over hastened-death has been intensifying in the latest years in Portugal (Marina, Costa-Maia, & Ricou, 2019). Two moments of particularly intense debate took place, as the Portuguese Parliament voted bills intending to decriminalize euthanasia in Portugal (2018 and 2020). On February 20th 2020, the bills were approved. Still, it is important to dive into the questions this practice raises. This study is divided in two - first, we present the empirical study we conducted to study the link between spirituality and agreeability with euthanasia; second, we present the validation of a scale of agreeability with spiritual beliefs in medical students. The empirical work focuses on the impact of common spiritual beliefs regarding metaphysical questions in agreeability with euthanasia. A sample of 497 Portuguese medical students was collected. Differences between genders and religious ideologies and the association between spiritual beliefs and opinion towards euthanasia cases were assessed. Possible predictors for agreeability with euthanasia were studied. Respondents were mostly favourable to the practice of euthanasia. Both formal religious affiliation and higher levels of religiosity significantly associated with lesser agreeability with euthanasia. Statistically significant association was found between every euthanasia scenario and multiple of the spiritual beliefs used. A number of spiritual beliefs constituted predictors of agreeability. We discuss the implications of religion and spirituality in agreeability with euthanasia. Using this sample, we validated a 9-item scale of agreeability with spiritual beliefs in medical students, from which two factors result - religion-based spirituality and non-religious spirituality. Further research is required to better understand the true weight of spirituality in one's opinion towards this ethical dilemma.